Journal of technical education seience No.52 (Ho Chi Minh city Ho Chi Minh city University of Technology and Education, 2019)
Contents: forecasting transient stability of power system by an ensemble classifier; analyzing the effect of value stream mapping via simulation in garment production line: a case study; limit analysis for plane stress problem by using nurbs based on bézier extraction in combination with second order cone program;....